Economic foundations for implementing x-ray machines in multidisciplinary hospitals - Khamidov Obid Abdurakhmanovich; Uma rov Farrukh Umarovich (THE INNOVATION ECONOMY, 2026)
The implementation of modern X-ray equipment in multidisciplinary hospitals is an integral part of con temporary medical and technological progress. This article analyzes the economic costs associated with the acquisition, installation, operation, and maintenance of X-ray equipment. Economic efficiency is evaluated using methods such as cost-benefit analysis (CBA) and health technology assessment (HTA). Furthermore, the experience of medical institutions in both public and private sectors is compared.